Place Branding through Establishing IP Mascot to Increase Economy in Indonesia using Pentahelix Model - Chaysalina, Inne (VCD: Journal of Visual Communication Design, 2023)
Indonesia has a diversity of cultures, each of which has its uniqueness. The characteristics of a region can be the basis for forming an Intellectual Property (IP) in the form of a mascot. The presence of an IP Mascot can improve the branding performance of the region. This research uses a descriptive qualitative method with a literature review comparing several case study areas are discussed. This research will specifically discuss the benefits of IP Mascots as a means of communication in a region based on the case studies raised. Based on the results, an attractive mascot design can build a region's branding image because an attractive mascot will be easier for the public to remember. Mascots can also increase consumer appeal and familiarity with a region. This research will also discuss the form of recommendations for the participation of various parties using the Pentahelix Model. It refers to coordination and collaboration towards the synergy of Pentahelix Actors to implement the role of it at tourism locations that use IP Mascot as a form of promotional media.